Synthesis and characterization of shelf-healing mortar with modified strength - Huseien, Ghasan Fahim (Penerbit UTM Press, 2015)
Cementitious materials being the most prospective building blocks achieving their absolute strength to avoid the deterioration in the early stage of service life is ever-demanding. Minimizing the labor and capital-intensive maintenance and repair cost is a critical challenge. Thus, self-healing mortars with modified strength are proposed. Lately, self-healing of micro-cracks by introducing bacteria during the formation of mortar or concrete became attractive. Self-healing with polymeric admixtures is considered to be relatively more durable and faster process. Certainly, the self-healing of synthetic polymeric materials is inspired by biological systems, where the damage triggers an autonomic healing response. This emerging and fascinating research initiative may significantly improve the durability and the safety limit of the polymeric components potential for assorted applications. In this work, using epoxy resin (diglycidyl ether of bisphenol A) without any hardener as admixture polymeric-cementitious materials is prepared. These epoxy-modified mortars are synthesized with various polymer-cement ratios subjected to initial wet/dry curing (WDC) together with long term dry curing (DC). Their self-healing function and hardening effects are evaluated via preloading and drying of the specimens, chemical analysis, and ultrasonic pulse velocity testing. It is demonstrated that 10% of polymer is the best proportion for polymer-cement ratio. Furthermore, the wet/dry curing is established to be superior process for healing hairline cracks present in the mortar. The excellent features of the results suggest that our novel method may constitute a basis for improving the compressive strength and self-healing features of mortars.